2019
DOI: 10.1155/2019/4530491
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Cornelia de Lange Syndrome: Difficulty in Prenatal Diagnosis

Abstract: We report a case of Cornelia de Lange syndrome (CdLS) where prenatal diagnosis was not made even with major anomaly. A 33-year-old Japanese woman was referred to our institution at 23 weeks of gestation because of fetal forearm defect. Ultrasound examination revealed short forearms and short humeri and femurs (–2.1 SD). The fetal estimated body weight was 450 g (–1.3 SD). Fetal MRI at 26 weeks of gestation revealed short forearms and hypoplasty of hand fingers. Fetal growth restriction became evident thereafte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 6 publications
0
2
0
3
Order By: Relevance
“…El síndrome Cornelia de Lange (CLS), es un desorden genético con una gran variabilidad fenotípica, caracterizado por alteraciones faciales, retraso psicomotor y malformaciones de las extremidades superiores, entre otras características clínicas. (2) Mundialmente se reporta una incidencia de 1:30.000 de los nacidos vivos (Dowsett , 2018) Paciente masculino, nacido por parto normal a las 38,4 semanas de edad gestacional, producto de primera gesta, parto normal. Al nacimiento fue atendido por el Servicio de Neonatología del Hospital Carlos Andrade Marín el día 10 de diciembre de 2018, con fenotipo sugerente de síndrome Cornelia de Lange.…”
Section: Introducción Presentación Del Casounclassified
“…El síndrome Cornelia de Lange (CLS), es un desorden genético con una gran variabilidad fenotípica, caracterizado por alteraciones faciales, retraso psicomotor y malformaciones de las extremidades superiores, entre otras características clínicas. (2) Mundialmente se reporta una incidencia de 1:30.000 de los nacidos vivos (Dowsett , 2018) Paciente masculino, nacido por parto normal a las 38,4 semanas de edad gestacional, producto de primera gesta, parto normal. Al nacimiento fue atendido por el Servicio de Neonatología del Hospital Carlos Andrade Marín el día 10 de diciembre de 2018, con fenotipo sugerente de síndrome Cornelia de Lange.…”
Section: Introducción Presentación Del Casounclassified
“…CdLS is typically diagnosed after birth based on some abnormal phenotypes (Kinjo et al, 2019 ). Although several cases have been reported before birth, prenatal diagnosis is still a challenge for clinicians and geneticists, with only 23% of all cases being detected prenatally (Avagliano et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although several cases have been reported before birth, prenatal diagnosis is still a challenge for clinicians and geneticists, with only 23% of all cases being detected prenatally (Avagliano et al, 2017 ). It has been reported that maternal serum pregnancy-associated placental protein-A (PAPP-A) produced by the placenta in the first and second trimester of pregnancy is an early indicator of CdLS, but it is not specific as only a very low level can support this diagnosis (Kinjo et al, 2019 ). At present, prenatal diagnosis of CdLS primarily relies on sonographic findings during the second and third trimester of pregnancy, such as characteristic facial features and congenital malformations.…”
Section: Introductionmentioning
confidence: 99%
“…Características como microcefalia, micrognatia, micromelia, aspectos faciais distintos, restrição de crescimento, atraso psicomotor, deficiência intelectual e malformações dos membros superiores, anomalias de desenvolvimento das mãos e pés, hirsutismo, crescimento excessivo de cabelos, sobrancelhas grossas, synophrys (crescimento de sobrancelhas na linha média para formar uma grande sobrancelha confluente), cílios longos, estrabismo, nariz pequeno com narinas antevertidas, filtro longo, boca abaixada, mamilos e umbigos hipoplásicos e contratura em flexão dos cotovelos são mais comuns de serem vistas nos indivíduos com a síndrome (Kinjo et al, 2019;Toker et al, 2009). Além dessas características, também podemos observar disfunções gastroesofágicas, cardíacas, oftalmológicas, anomalias geniturinárias, estenose pilórica, hérnia diafragmática congênita, defeitos nos septos cardíacos, perda auditiva e tendências a autoagressão também ocorrem com frequência (França et al, 2009).…”
Section: Introductionunclassified
“…Em relação a respeito das alterações cranianas, é observado a presença da microcefalia em alguns casos. Na face é perceptível a presença de um nariz pequeno, os olhos apresentam estrabismos, ptose e nistagmo, as pestanas são compridas e enroladas, e em alguns casos apresentam sobrancelhas espessas (Kinjo et al, 2019;Toker et al, 2009). As principais manifestações orais são relatadas na mandíbula são: a macroglossia, sínfise proeminente, macrognatia e esporas no ângulo anterior da mandíbula.…”
Section: Introductionunclassified